Analisis Karakteristik Dan Laju Angkutan Sedimen Total Saluran Rawasari Indah Kota Tarakan - Rahmat Faizal; Jean Timoti; Aswar Amiruddin (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
Embung as one of the waterworks that serves as a reservoir for water, Embung Rawasari Indah is one of the 5 reservoirs in Tarakan yann city currently experiencing silting due to sedimentation process, which causes the water discharge flowing towards the reservoir to be not optimal. The purpose of this study was to determine the characteristics and discharge of total sediment transport in Rawasari indah Channel and obtain a comparison of three methods of calculating the total sediment transport in Rawasari Indah Channel. Based on the results of laboratory tests sediment classification is dominated by fine sand, very fine sand and medium sand. The results of the study obtained the average value of sediment transport discharge on Engelund and Hansen's method is 1.382998513 tons/year, the method is 15.88046241 tons/year, Laursen method is 2.000124533 tons / year. Based on the calculation results with the largest value, the method chosen as a benchmark in the calculation of sediment transport.